18. PARENTS' INTENTION TO VACCINATE STUDENTS AGAINST HPV AT QUANG TRUNG HIGH SCHOOL IN TAY NINH PROVINCE (Vietnam Journal of Community Medicine, 2024)
Aim: To determine the percentage of parents who intend to vaccinate students with the HPV vaccine at Quang Trung High School in Tay Ninh Province and related factors.Method: A descriptive cross-sectional study was conducted on 448 parents between January and May 2024, using cluster and random sampling methods. The data was collected by a self-fulfillment questionnaire designed based on the Theory of Planned Behavior and Health Belief Model. A generalized linear model was performed to determine the association between vaccination intention and associated factors.Result: The percentage of parents who intend to vaccinate their children with the HPV vaccine was 50.2%. The study found a statistically significant association between HPV vaccination intention with age group, education level, income, knowledge of HPV, factors in the Health Belief Model and Planned Behavior theory with p < 0.05.Conclusion: The percentage of parents who intend to vaccinate their children with the HPV vaccine accounts for about half of the sample population. Therefore, there is a need for health education interventions that focus on elements of the Health Belief Model and Planned Behavior theory, not only to improve parents' beliefs and perspectives but also to increase coverage of the HPV vaccine among parents and students.
Keywords: Knowledge, Health Belief Model (HBM), HPV vaccine, intention, Theory of Planned Behavior (TPB)